On Manuscripts, Prints and Blessed Transformations: Caterina da Siena’s Legenda maior as a Model of Sainthood in Premodern Castile - Pablo Acosta-García (Religions, 2020)
In this article, I analyze the translation commissioned in 1511 by Cardinal Francisco Ximénez Cisneros of the Life of Catherine of Siena by Raimundo da Capua, which includes the legendae of Giovanna (also known as Vanna) da Orvieto and Margherita da Città di Castello in the light of its translation, commission, and reception in premodern Castile. In the first place, I clarify the medieval transformations of Caterina’s text by discussing the main branches of her manuscript tradition and explaining the specificities of the editions authorized by Cisneros in order to know what exactly was printed. In the second place, I put these specificities into the courtly, prophetic context in which those books were published. Finally, I analyze the reception of these editions in the Iberian Peninsula, especially in relation to the figure of María de Santo Domingo, the famous Dominican tertiary.